Light-related photosynthetic characteristics of lotic macroalgae - Necchi, O. (Kluwer Academic Publ, 2004)
Photosynthetic characteristics in response to irradiance were analysed in 42 populations of 33 macroalgal species by two distinct techniques (chlorophyll fluorescence and oxygen evolution). Photosynthesis-irradiance (PI) curves based on the two techniques indicated adaptations to low irradiance reflected by low saturation values, high to moderate values of photosynthetic efficiency (alpha) and photoinhibition (beta), for Bacillariophyta and Rhodophyta, which suggests they are typically shade-adapted algae. In contrast, most species of Chlorophyta were reported as sun adapted algae, characterized by high values of I-k and low of alpha, and lack of or low photoinhibition. Cyanophyta and Xanthophyta were intermediate groups in terms of light adaptations. Photoinhibition was observed in variable degrees in all algal groups, under field and laboratory conditions, which confirms that it is not artificially induced by experimental conditions, but is rather a common and natural phenomenon of the lotic macroalgae. Low values of compensation irradiance (I-c) were found, which indicate that these algae can keep an autotrophic metabolism even under very low irradiances. High ratios (>2) of photosynthesis/respiration were found in most algae, which indicates a considerable net gain. These two physiological characteristics suggest that macroalgae may be important primary producers in lotic ecosystems. Saturation parameters (I-k and I-s) occurred in a relatively narrow range of irradiances (100-400 mumol photons m(-2) s(-1)), with some exceptions (higher in some filamentous green algae or lower in red algae). These parameters were way below the irradiances measured at collecting sites for most algae, which means that most of the available light energy was not photochemically converted via photosynthesis. Acclimation to ambient PAR was observed, as revealed by lower values of I-k and I-c and higher values of alpha and quantum yield in algae from shaded streams, and vice versa. Forms living within the boundary layer (crusts) showed responses of shade-adapted species and had the highest values of P-max, alpha and quantum yield, whereas the opposite trend was observed in gelatinous forms (colonies and. laments). These results suggests adaptation to the light regime rather than functional attributes related to the growth form.
Keywords: chlorophyll fluorescence; irradiance; lotic; Macroalgae; oxygen evolution; photosynthesis